Social Processes of Knowledge of Technological Capabilities and Intellectual Capital on New Technology-Based Firms (Global Journal of Management and Business Research, 2015)
This paper proposes that social processes of knowledge developed by innovative firms are core factors of Technological Capability and Technological Capital, they are the same processes and they are also a critical key to get competitive sustainable advantages. From the Resource-Based View approach, the Dynamics Capabilities approach and the Knowledge-Based Theory of the firm, the importance of knowledge as a key ingredient of technology must be emphasized and its importance to find the way back to the economic growth. We investigate that when the members of an innovative firmcreate and develop their firm#x2019;s Technological Capabilities, using social processes of knowledge, they are also creating and exploiting the firm#x2019;s IntellectualCapital.
Keywords: intellectual capital; new-technology-based firms; social processes of konowledge; technological capital; technological capability